Probability of winning a badminton game: the relationship between unforced errors and winner points - Cren Chiminazzo, J. G.; Barreira, J.; Cabello-Manrique, D. (Science and Racket Sports VI, 2019)
The unforced errors (UE) and winner points (WP) are the notational analysis most used as performance indicators in badminton matches. Winner players perform significantly more WP, while loser players perform more UE. However, it is unknown how the interaction between UE and WP may influence the match outcome. The aim of this study was to calculate the probability of winning a game of badminton based on the two events, UE and WP, occurring together. All men single matches (n=56) from the 2016 Olympic Games were recorded and analysed. The binomial logistic regression was used to calculate the probability of winning a game. The game outcome was considered as dependent variable (Victory=1, Loss=0) and the frequency of UE and WP as independent variables. We found that a frequency greater than 10 WP and fewer than 5 UE present a high probability (>80%) of winning a game. On the other hand, frequencies above 9 UE and under 6 WP distance the athlete from the victory (<20%). When the number of UE becomes greater than the WP, the probability of victory decreases significantly. The results of this study provide valuable information for the decision-making of coaches and athletes during the matches.